PENDIDIKAN AQIDAH DALAM HADIS NABAWI SEJAK BALITA HINGGA LANSIA - Aguswan Rasyid (Ensiklopedia of Journal, 2020)
Islamic education is a very comprehensive education, because its scope includes various aspects, from education in aqidah, worship, morals, reason, intellectual, sexuality, socio-culture to physical education. This aims to produce qualified, submissive and obedient beings to the Creator (al-Khaliq), useful for religion and the nation and beneficial for humans and the environment. To realize this noble goal, one of the educational materials that must be taught to children and students to be known, understood and applied in everyday life is aqidah education. In this paper, aqidah education will be revealed from the perspective of the hadith of the Prophet. It turned out that according to the hadith of the Prophet. Aqidah education must be introduced to children from an early age, since being born into the world continuously in childhood, adolescence, adulthood and in the elderly (elderly) and ended before dying, passing away. The concept of lifelong aqidah education presented by the Prophet's hadiths shows the very importance of aqidah in the life of Muslims in particular and humans in general.